2018
DOI: 10.3389/fevo.2018.00109
|View full text |Cite
|
Sign up to set email alerts
|

Was Mesosaurus a Fully Aquatic Reptile?

Abstract: Mesosaurs have been considered strictly aquatic animals. Their adaptations to the aquatic environment are well known and include putative viviparity, along with the presence of several skeletal characters such as a long, laterally compressed tail, long limbs, the foot larger than the manus, and presence of pachyosteosclerotic bones. They were also described as possessing non-coossified girdle bones and incompletely ossified epiphyses, although there could be an early fusion of the front girdle bones to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 115 publications
(190 reference statements)
4
24
1
Order By: Relevance
“…However, mesosaurs may have had the ability to occasionally come up onto land 31 , and the ability to escape potential terrestrial predators using caudal autotomy in order to return to the water would have been beneficial. Furthermore, it has been suggested that mesosaurs may have been cannibalistic, with adults preying on juveniles 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, mesosaurs may have had the ability to occasionally come up onto land 31 , and the ability to escape potential terrestrial predators using caudal autotomy in order to return to the water would have been beneficial. Furthermore, it has been suggested that mesosaurs may have been cannibalistic, with adults preying on juveniles 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The Permian family Mesosauridae is involved in several key events of the history of life and that of natural sciences. First of all, mesosaurs are exclusively found in early Permian black-shale and limestone deposits from both southeastern South America (the Irati Formation in southern Brazil and the Melo Formation in Uruguay) and southwestern Africa (the Whitehill Formation in Namibia and in western South Africa) (Oelofsen and Araújo, 1987). Because of this geographical distribution, which supports the theory that the two continents were once connected, mesosaurs were among the fossils cited by Alfred Wegener as a line of evidence to corroborate his theory of continental drift (Du Toit, 1937).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies place them among Parareptilia (e.g. Modesto, 2006 Dougall et al, 2017Dougall et al, , 2018Tsuji and Müller, 2009), whereas others suggest that mesosaurs may instead represent the basalmost clade of Reptilia sensu Modesto and Anderson (2004) (Laurin and Reisz, 1995;Laurin and Piñeiro, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesosaurs, known from the Early Permian of southern Africa, Brazil and Uruguay, are the oldest known amniotes with a primarily, though probably not strictly, aquatic lifestyle (Nuñez Demarco et al, 2018). Despite having attracted attention of several prominent scientists, such as Wegener (1966), who used them to support his theory of continental drift, and the great anatomist and paleontologist von Huene (1941), who first suggested the presence of a lower temporal fenestra in Mesosaurus, several controversies still surround mesosaurs.…”
Section: Introductionmentioning
confidence: 99%